Gradual evolution of allopolyploidy in Arabidopsis suecica - Burns, Robin; Mandáková, Terezie; Gunis, Joanna; Soto-Jiménez, Luz Mayela; Liu, Chang; Lysak, Martin A; Novikova, Polina Yu; Nordborg, Magnus (Nature ecology & evolution, 2021)
Most diploid organisms have polyploid ancestors. The evolutionary process of polyploidization is poorly understood but has frequently been conjectured to involve some form of 'genome shock', such as genome reorganization and subgenome expression dominance. Here we study polyploidization in Arabidopsis suecica, a post-glacial allopolyploid species formed via hybridization of Arabidopsis thaliana and Arabidopsis arenosa. We generated a chromosome-level genome assembly of A. suecica and complemented it with polymorphism and transcriptome data from all species. Despite a divergence around 6 million years ago (Ma) between the ancestral species and differences in their genome composition, we see no evidence of a genome shock: the A. suecica genome is colinear with the ancestral genomes; there is no subgenome dominance in expression; and transposon dynamics appear stable. However, we find changes suggesting gradual adaptation to polyploidy. In particular, the A. thaliana subgenome shows upregulation of meiosis-related genes, possibly to prevent aneuploidy and undesirable homeologous exchanges that are observed in synthetic A. suecica, and the A. arenosa subgenome shows upregulation of cyto-nuclear processes, possibly in response to the new cytoplasmic environment of A. suecica, with plastids maternally inherited from A. thaliana. These changes are not seen in synthetic hybrids, and thus are likely to represent subsequent evolution.
Keywords: Hybridization, Genetic; Diploidy; hybridizace genetická; Polyploidy; lidé; Genome, Plant; diploidie; genom rostlinný; Arabidopsis; Humans; polyploidie